Anti-inflammatory potential of artificial microcapsules containing thalidomide for use in treating Crohn's disease - Fakhoury, Marc (Journal of Drug Delivery and Therapeutics, 2013)
Crohn's disease is a chronic inflammatory bowel disease associated with an abnormal immune response in the gastrointestinal tract. Several studies demonstrate that thalidomide could be effective in the treatment of refractory Crohn's disease. However, its widespread use has been limited because of potential side effects. In the present study, we investigated the inhibitory activity of alginate-poly-L-lysine-alginate (APA) microcapsules containing thalidomide on Lipopolysaccharide (LPS)-induced inflammation in RAW 264.7 macrophage cells and on 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced Crohn’s disease. Results showed that APA microcapsules containing thalidomide inhibited the release of pro-inflammatory cytokines in cell supernatant following LPS activation. Moreover, treatment with microencapsulated thalidomide decreased the level of TNF-α, IL-6 and IL-1β by 49.3%, 62.3% and 54.6% respectively in TNBS-treated mice. The present project validates the efficiency of APA microcapsules in providing a targeted delivery of thalidomide for treating chronic conditions such as Crohn’s disease.